(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The theme of Indian English drama is begin form the ancient period to the today’s present era that deal with the history, mythology and so on. After about 18th century many plays written in literature, which is in an Indian languages were adopted into Indian English drama. Vijay Tendulkar had a remarkable and high place in the Indian theatrical literature world. He was also recognized as a famous Marathi playwright and screenwriter in the world of cinema and television. Girish Karnad was a noted Kannada playwright, Indian actor, director and screenwriter who made his mark in the fields of Indian theatre, cinema and literature. While in ‘Sakharam Binder’ Tendulkar explores with great objectivity of married abandon woman Laxmi and Champa the complication in human nature due to the sex and violence. Karnard’s ‘Nagamandala’ Rani suffers endless torture. Rani’s husband Appanna treats her like a slave, neglecting Rani’s physical and emotional needs. When Appanna found that his wife Rani is pregnant he became furious and thinks that Rani has taken secret lover (Naga). Appanna then tries to kill Rani with her pregnancy and finally drags her two village court.